2007
DOI: 10.1093/sleep/30.7.829
|View full text |Cite
|
Sign up to set email alerts
|

Changes in REM-Sleep Percentage Over the Adult Lifespan

Abstract: Ability to detect both linear and nonlinear change in REM%, REM minutes, and total sleep time over the lifespan was useful for resolving inconsistent findings about the existence of changes in REM% with aging. This approach to research synthesis also facilitated identification of ages for which little normative information about REM sleep was available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 29 publications
(51 reference statements)
1
32
0
2
Order By: Relevance
“…While sleep duration and quality have been reported to decline with age across adulthood (Floyd et al, 2007), robust associations have not consistently been observed (Reyner et al, 1995) and may depend on sampling factors such as the health status of study participants (Bliwise, 1993). Indeed, recent studies controlling for health factors have observed increases in sleep quality across adulthood into old age (Grander et al, 2012; Luca et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…While sleep duration and quality have been reported to decline with age across adulthood (Floyd et al, 2007), robust associations have not consistently been observed (Reyner et al, 1995) and may depend on sampling factors such as the health status of study participants (Bliwise, 1993). Indeed, recent studies controlling for health factors have observed increases in sleep quality across adulthood into old age (Grander et al, 2012; Luca et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…However, as we age, there tends to be a shift in REM sleep to earlier in the night, resulting in a slightly decreased latency to REM sleep [ 7,9 ] . Also, a decrease of approximately 0.6% per decade in percentage of REM sleep [ 7,8 ] has been reported [ 10 ] , but this trend toward decreased REM percentage has not been found in all studies [ 9 ] .…”
Section: Changes In Sleep Architecture As We Agementioning
confidence: 92%
“…In phylogeny, this function of REM sleep is advantageous to explain the various exceptions of REM sleep, especially the absence of REM sleep in dolphins (Cai, 2015b;Lyamin et al, 2007;Madan & Jha, 2012;Sekiguchi et al, 2006;Siegel, 2008) and short duration of REM sleep in birds (Ayala-Guerrero et al, 1988Cai, 2015b) in contrary to that in humans (Cai, 2015b;Floyd et al, 2007) and rodents (Cai, 2015b;Rechtschaffen et al, 1989), the absence of penile erections in REM sleep in armadillo (Affanni et al, 2001;Cai, 2015b), as well as the higher voltage in EEG during REM sleep in platypus (Cai, 2015b;Siegel et al, 1998;1999) and ostrich (Cai, 2015b;Lesku et al, 2011). In physiology, this function of REM sleep is advantageous to explain the association of REM sleep with the atonic episodes in SWS (Cai, 2015b;Tinguely et al, 2006;Werth et al, 2002), the absence of drastic menopausal change in duration of REM sleep (Cai, 2015b;Kalleinen et al, 2008;Orff et al, 2012;Shaver et al, 1988), and the different effects of ambient temperature on duration of REM sleep in rodents (Amici et al, 1998;Cai, 2015b;Rosenthal & Vogel, 1993;1994;Roussel et al, 1984) and humans (Cai, 2015b;Haskell et al, 1981;Karacan et al, 1978).…”
Section: The Peripheral Functions Of Rem Sleepmentioning
confidence: 99%
“…In accordance, even though there is drastic decrease in sexual drive in menopause, there is little menopausal change in duration of REM sleep, disagreeing with the brain function of REM sleep for conflict of emotional memories against disinhibited drives in humans, while supporting the function of REM sleep as improvement of muscular efficiency relatively. As the REM sleep declines roughly with aging (Floyd et al, 2007), immobility is obviously neither the major function of REM sleep in humans.…”
Section: Rem Sleep and Menopausementioning
confidence: 99%